2013
DOI: 10.1016/j.rmed.2012.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Common intronic D variant of ACE gene is associated with endothelial dysfunction in COPD

Abstract: These findings suggest possible association of the functional ACE D allele with altered vascular responses that may modulate development of distinct COPD symptoms. The results are obtained in a limited clinical cohort, and deserve repeated trials in other groups of COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Seventeen original studies used ultrasound-based FMD to determine endothelial function in patients with COPD ( Figure 1, Table 1 and 2) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A total number of 1228 participants was evaluated: 724 patients with a spirometry-based diagnosis of COPD (71% men; mean age: 65±5 years; body mass index (BMI): 27±2 kg/m 2 ) and 504 controls (56% men; mean age: 62±8 years; BMI: 27±2 kg/m 2 ) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen original studies used ultrasound-based FMD to determine endothelial function in patients with COPD ( Figure 1, Table 1 and 2) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A total number of 1228 participants was evaluated: 724 patients with a spirometry-based diagnosis of COPD (71% men; mean age: 65±5 years; body mass index (BMI): 27±2 kg/m 2 ) and 504 controls (56% men; mean age: 62±8 years; BMI: 27±2 kg/m 2 ) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies from the total of 17 were not included in the meta-analyses because the studies only measured patients with COPD and did not include a control group [24,25,34,36]; three of these focused on determinants of endothelial function [24,25,34] and one studied the effect of lung volume reduction surgery on endothelial function in patients with COPD [36]. Additionally, three studies were excluded from the analysis since percentage mean change in brachial artery diameter and standard deviation were not available, even after contacting the corresponding authors [22,37,38].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the deletion polymorphism, the D allele, of the ACE gene is associated with a higher ACE activity [20], and an elevation of the ACE activity was observed in COPD patients [43]. Therefore, the associations between ACE polymorphism and COPD have been investigated in many previous studies [1316, 26, 28, 31, 44, 45]. However, the results of previous studies regarding the association between ACE polymorphism and COPD were conflicting and contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme (ACE), a regulatory protein with both vascular and collagenolitic effects has different variants. The D variant is associated with both endothelial dysfunction and number of exacerbations in patients with COPD and thus may also play a role in the development of endothelial dysfunction [127]. …”
Section: Introductionmentioning
confidence: 99%
“…A randomised control trial (RCT) of statin therapy in COPD patients also demonstrated that statins reduced the level of systemic inflammatory markers seen in these patients and also improved endothelial function in patients with evidence of raised systemic inflammation [136]. The ACE D variant is associated with increased production of ACE suggesting that perhaps ACE inhibitor drugs (already available for other conditions such as hypertension) may provide another treatment option for this subgroup of patients [127]. Rho-kinase inhibitors have also improved NO release from endothelial cells in vitro suggesting that blocking this pathway may provide another means to improve endothelial dysfunction [137].…”
Section: Introductionmentioning
confidence: 99%